TUC Anti - Privatisation Campaign leaflet, 1984 (1984)
1984 1960-2000 "TUC Anti - Privatisation Campaign leaflet, 1984" [T0582.jpg], 1984 In 1983, the TUC launched a campaign in opposition to privatisation moves in the National Health Service, local government and the nationalised industries. In March 1984, a package of campaign materials under the slogan "Public its yours Private its theirs" used the symbol of vultures to suggest an alternative motive for the Governments privatisation programme.